A musculoskeletal model to estimate the relative changes in wrist strength due to interacting wrist and forearm postures. Issue 13 (3rd October 2017) - La Delfa, Nicholas J.; Potvin, Jim R.
Abstract: Wrist rotations about one wrist axis (e.g. flexion/extension) can affect the strength about another wrist axis (e.g. radial/ulnar deviation). This study used a musculoskeletal model of the distal upper extremity, and an optimization approach, to quantify the interaction effects of wrist flexion/extension (FE), radial/ulnar deviation (RUD) and forearm pronation/supination (PS) on wrist strength. Regression equations were developed to predict the relative changes in strength from the neutral posture, so that the changes in strength, due to complex and interacting wrist and forearm rotation postures, can be incorporated within future ergonomics assessments of wrist strength.